The Effect of Project-Based Learning Integrated STEM Toward Critical Thinking Skill (Journal of Primary Education, 2019)
The global challenge needs people who can solve the problem in everything. Students can't solve the problem well. It caused by the lesson only for memorizing, so student’s critical thinking skill is not yet maximum. This study aims to identify the effect of project-based learning integrated STEM toward critical thinking skill of students. The method of this study was quasi-experimental with pre-test – post-test control group design. Sampling technique was used nonprobability sampling. Data collection technique used description test critical thinking skill. Data analysis used N-gain score test and t-test. The result of t-test student’s critical thinking skill showed sig (2-tailed) 0.002 it means there was a different average in critical thinking skill between experiment class and control class. The average of experiment class was higher than the control class. It showed that the implementation of project-based learning lesson integrated STEM affected towards student’s critical thinking skill.